Selection of experimental strawberry (Fragaria x ananassa) hybrids based on selection indices - Vieira, S. D.; de Souza, D. C.; Martins, I. A.; Ribeiro, G. H.M.R.; Resende, L. V.; Ferraz, A. K.L. [UNESP]; Galvão, A. G.; de Resende, J. T.V. (Genetics and Molecular Research, 2017)
The strawberry (Fragaria x ananassa Dutch.), is the only vegetable belonging to the rosacea family. All strawberry species have now emerged from wild species and belong to the genus Fragaria, being that this genus presents more than 45 described species, and only 11 are considered natural species. Due to the octoploid nature of strawberry and its variability after hybridization, selecting one or more characters may result in unfavorable genotypes and even the exclusion of promising ones, because negative genetic correlations have been observed among them that cause inefficient selection. Therefore, the objective of this study was to verify the efficiency of selection indices in selecting experimental strawberry hybrids for in natura consumption and processing. Seven commercial cultivars and 103 hybrids were used, which were obtained from populations derived from their crossings. The experiment was conducted in augmented blocks, in which four agronomical traits (total mass, amount of commercial fruit, amount of noncommercial fruit, and average fruit mass) and seven physical-chemical traits (soluble solids, soluble solids:titratable acidity ratio, total sugars, total pectin, vigor, and internal and external coloration) were evaluated. For hybrid selection, the following indices were used: Mulamba and Mock (1978), Smith (1936), Hazel (1943), and genotype-ideotype, which selected 20% of the genotypes evaluated. The three indices selected about 9% of the hybrids. The selection of two experimental hybrids (89 and 495) and the use of selection indices resulted in larger estimates of selection gains. The Mulamba and Mock (1978), Smith (1936), and Hazel (1943) indices had the highest percentage of gains on selection, and are therefore recommended for the selection of strawberry clones.
Keywords: Agronomical trait; Experimental hybrid; Plant breeding; Selection index; Strawberry